Suboptimal Responses in Chronic Myeloid Leukemia - Jabbour, Elias (Wiley Subscription Services, Inc., A Wiley Company, 2012)
The high response rates and increased survival associated with imatinib therapy prompted a paradigm shift in the management of chronic myeloid leukemia. However, 25% to 30% of imatinib-treated patients develop drug resistance or intolerance, increasing the risk of disease progression and poor prognosis. In 2006, the European LeukemiaNet proposed criteria to identify patients with a suboptimal response to, or failure associated with, imatinib; these recommendations were updated in 2009. Suboptimal responders represent a unique treatment challenge. Although they may respond to continued imatinib therapy, their long-term outcomes may not be as favorable as those for optimally responding patients. Validation studies demonstrated that suboptimal responders are a heterogeneous group, and that the prognostic implications of suboptimal response vary by time point. There are few data derived from clinical trials to guide therapeutic decisions for these patients. Clinical trials are currently underway to assess the efficacy of newer tyrosine kinase inhibitors in this setting. Identification of suboptimal responders or patients failing treatment using hematologic, cytogenetic, and molecular techniques allows physicians to alter therapy earlier in the treatment course to improve long-term outcomes. Cancer 2012;. © 2011 American Cancer Society.